Large decline in the abundance of a targeted tropical lethrinid in areas open and closed to fishing - McLean, D.; Harvey, Euan; Fairclough, D.; Newman, Stephen (Inter-Research, 2010)
In Western Australia, one of the most important commercially and recreationally targeted, yet understudied fish species is the redthroat emperor Lethrinus miniatus. The present study aimed to compare the relative abundance and size of L. miniatus in areas open and closed to fishing at the Houtman Abrolhos Islands and to assess change in these populations over a 5 yr period. Baited remote underwater stereo-video systems (stereo BRUVs) were used to conduct the surveys from 2005 to 2009, which included different depths and locations across 4 geographically separated groups of islands. Data showed high spatial variability in the relative abundance of L. miniatus across depths, sites, and island group locations. In 2005 and 2006, L. miniatus were more abundant at depths of 22 to 26 m than in 8 to 12 m. At this time, individuals were also 1.3x more abundant and 10% larger in length in areas closed to fishing than in areas open to fishing. Starting in 2007, however, relative abundances of L. miniatus declined so markedly that in 2009 only 20 % of the 2005 and 2006 numbers remained. This decline removed the disparity between depths, closed areas and fished locations. Unlike with relative abundance, L. miniatus remained consistently larger inside closed areas (mean 370 mm fork length) than in areas open to fishing (mean 350 mm). Of the 483 individuals measured across the 5 yr of the study, 98 % were larger than the minimum legal size for retention, and therefore subject to harvest. Mean lengths increased each year, as the size structure of the population reflected an aging cohort. With declines in measured relative abundance in excess of 80% over the past 5 yr, the sustainability of L. miniatus assemblages at the Houtman Abrolhos Islands is in question